Keefektifan Model Somatic Auditory Visualization Intellectualy Berbantu Media Konkret terhadap Keterampilan Proses Sains - Desy Erviana; Sukamto Sukamto; Arfilia Wijayanti (STKIP Andi Matappa Pangkep, 2023)
The background that prompted this research was because the students lacked science process skills, the percentage of test results was still low on the science process skills indicator, and the teacher did not use interesting learning media. The aim of the research is to know the effectiveness of somatic auditory visualization intellectualy assisted by concrete media to be effective on the science process skills of V students at SD Negeri 01 Karangasem. The method used is a quantitative method. The results of non-parametric statistical analysis using the Wilcoxon sign test analysis technique were 10,716 and ttable was obtained at 2.009 at a significant level of 5%, meaning tcount (10,716) > ttable (2,009), it can be concluded that the somatic auditory visual intellectual model assisted by concrete media is effective for improvement of science process skills for class V SD Negeri 01 Karangasem.Â